PROTOTYPE OF A 4-DOF ROBOTIC ARM BASED ON ATMEGA328P MICROCONTROLLER USING POTENTIOMETER CONTROL SYSTEM - Tesalonika, Tesalonika (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2026)
The advancement of electronics and control systems has significantly boosted the use of robotics, particularly in addressing heavy, dangerous, dirty, and difficult tasks within Indonesia's expanding Industry 4.0 sector. This study emphasizes the role of robotics in Indonesia and reviews fundamental theories on robotic arms, covering their definition, history, kinematics, and essential components such as the ATmega328P microcontroller, Arduino Uno R3, MG90S servo motor, potentiometer, XL4015 step-down module, and I2C LCD module. The research focuses on developing and testing a 4-DOF robotic arm prototype that utilizes a potentiometer control system. The design process includes the creation of system block diagrams, frame and physical design, and electronic component configuration. The robotic arm's performance is evaluated through servo motors testing, which examines its movement radius and load-lifting capabilities. Results indicate that the robotic arm achieves a minimum movement radius of 10 cm with a 15 ° tolerance error and a maximum radius of 22 cm with a 1 ° tolerance error. Additionally, the arm's ability to lift and stabilize various loads is tested, with findings showing that the servo motors maintains stable and accurate operation across different angles and distances. These insights are crucial for optimizing the 4-DOF robotic arm prototype for practical applications.